Comparison of Simple Penile Dressings following Hypospadias Repair: does it really matter? - Syed Waqas Ali, Uzair Aslam, Saad Khalid, Syed Muhammad Ashraf Jahangeer, Muhammad Arif Mateen Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypospadias repair requires an appropriate wound dressing to prevent complications, but there is a lack of studies comparing the efficacy of different dressings. Aim: To compare the clinical outcomes of occlusive hydrocolloid dressing and petroleum-impregnated gauze with zinc oxide adhesive plaster, and recommend an appropriate dressing based on efficacy, availability, and cost-effectiveness. Methods: We performed a retrospective cohort study on paediatric patients who had undergone hypospadias repair between August 2017 and November 2020 at Dr. Ruth K. M. Pfau Civil Hospital Karachi, Pakistan. All the patients receiving one of the two wound dressings, occlusive hydrocolloid dressing (group A) or petroleum-impregnated gauze with zinc oxide adhesive plaster (group B) during primary or secondary hypospadias repair, operated by the same paediatric surgeon were included in this study. Patients with missing data were excluded. There was only one patient lost to follow up in this study. Results: A total of 64 male hypospadias patients with a mean age of 6.0 ± 3.4 years were included in this study. Group A patients (n=37) received a thick 10 x 10 cm occlusive hydrocolloid dressing whereas, in Group B patients (n=27), a 2.5 x 10 cm petroleum-impregnated gauze with zinc oxide adhesive plaster was applied over the wound. In group A, five patients (13.5%) suffered post-operative fistula and wound dehiscence. Whereas, in group B, the post-operative fistula was seen in three patients (11.1%). This study provides evidence-based information to clinicians and healthcare providers regarding the use of wound dressings for hypospadias repair. By demonstrating the efficacy of a cheaper and more accessible dressing, this study could help improve access to care and reduce costs for patients, especially in resource-limited settings. Conclusion: Occlusive hydrocolloid dressing and petroleum-impregnated gauze are equally effective in the healing of hypospadias repair wounds. The simpler and cheaper petroleum-impregnated gauze may be preferable in resource-limited settings. Keywords: Hydrocolloid dressing; Petroleum impregnated gauze; Paraffin gauze; Hypospadias